2023
DOI: 10.1101/2023.03.06.531302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunometabolic rewiring in long COVID patients with chronic headache

Abstract: Almost 20% of patients with COVID-19 experience long-term effects, known as post-COVID condition or long COVID. Among many lingering neurologic symptoms, chronic headache is the most common. Despite this health concern, the etiology of long COVID headache is still not well characterized. Here, we present a longitudinal multi-omics analysis of blood leukocyte transcriptomics, plasma proteomics and metabolomics of long COVID patients with chronic headache. Long COVID patients experienced a state of hyper-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…Our study confirmed and extended prior reports of metabolic dysregulation in Long Covid (6, 14, 15, 17, 18, 20, 22, 29). We also observed decreased activity of the telomere maintenance pathways and DNA damage recognition pathways in the LC group compated with the CC group, which may signal impaired tissue regeneration in patients with Long Covid (31, 32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirmed and extended prior reports of metabolic dysregulation in Long Covid (6, 14, 15, 17, 18, 20, 22, 29). We also observed decreased activity of the telomere maintenance pathways and DNA damage recognition pathways in the LC group compated with the CC group, which may signal impaired tissue regeneration in patients with Long Covid (31, 32).…”
Section: Discussionsupporting
confidence: 92%
“…Clinical symptoms in the Long Covid (LC) cohort included persistent fatigue, shortness of breath, exercise intolerance, brain fog, and abnormal smell and taste (Fig. 1b), similar to prior reports (3,5,(21)(22)(23)(24).…”
Section: Study Participantssupporting
confidence: 82%
“…Frequency of chronic headache range widely from ~8–40% among long COVID cases ( 46 , 63–65 ). Individuals mildly affected by SARS-CoV-2 infections seemed more prone to post-COVID headaches ( 64 , 66 ), which were exacerbated with a prior history of migraines ( 63 , 64 ). Our MR analysis showed a strong positive causal association between COVID-19 and chronic headache in long COVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our MR analysis showed a strong positive causal association between COVID-19 and chronic headache in long COVID patients. Recent evidence suggests that long COVID headaches appear to be triggered by hyperinflammation and are sustained by chronic inflammatory activation, and dysregulation of neurotransmitters and metabolic inflammation ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ICDH-3 provides guidance on how to choose the most-likely diagnosis. Headache is one of the most common neurologic symptoms reported in long COVID [39,40]. The World Health Organization de nes the post-COVID-19 condition or long COVID as new symptoms or the presence of symptoms for over two months, within three months following initial SARS-CoV-2 infection that cannot be explained by any other reason [41].…”
Section: Discussionmentioning
confidence: 99%